Cultural attitudes to the aged: An Indian perspective - P. Gounden; T. Puckree (AOSIS, 1999)
Institutionalization of elderly Indians seems to have been increasing with the aging of the twentieth century. This paper looks at Indian thought and cultural practice with regard to the elderly in time perspective.  Historically, although the main prescription to cultural practice and respect for the elderly came from the various Indian Scriptures, this was coloured by the specific needs of each society which changed when these societies were nomadic, settled farmers or were actively engaged in war. Later other factors like industrialization resulted in a breakdown of the extended family in which the father no matter how old or productive was the authority figure who demanded respect. This trend was also seen in published literature about the attitude of other nationalities towards their elderly. Health professionals have been grappling with the role of health care workers in achieving successful patients outcomes based on attitudes towards the elderly. More work needs to be done on this subject in this country.